Excited states in dye-based functional materials - Kondratenko, P.A.; Lopatkin, Yu.M.; Sakun, T.N. (Functional Materials, 2008)
Results of experimental and theoretical studies are considered concerning the processes running during a molecule relaxation from a high-excited state obtained both under a single-quantum (S₀->Sn) and a two-stage (S0 -ʰᵛ> S₁ -> T₁ -ʰᵛ> Tn) excitation. Polymeric layers containing dyes (resazurin, methylene blue, and brilliant green) have been used as the study objects. It has been established that in high-excited states the systems may live during several vibrations characterizing the specified states. The dissociative states have been shown to exist among the high-excited ones. This causes the quasi-equilibrium molecular dissociation processes, electron transfer between the high-excited molecule and its surrounding (matrix), etc., proceeding from those states. Such processes cause the dye fading on textiles, the dye instability in the course of laser radiation, etc. The dye photo-induced instability has been proposed to make use for information storage . Подано аналіз експериментальних та теоретичних досліджень процесів, які відбуваються при релаксації молекули з високозбудженого стану, одержаного як при одноквантовому (S₀->Sn), так і при двостадійному (S0 -ʰᵛ> S₁ -> T₁ -ʰᵛ> Tn) збудженні. Ян об'єкти дослідження використано полімерні шари з барвниками (резазурином, метиленовим блакитним та брильянтовим зеленим). З'ясовано, що у висонозбуджених елентронних станах системи здатні жити на протязі кількох наливань, що характеризують відповідні стани. Показано, що серед високозбуджених станів є дисоціативні стани. Це зумовлює перебіг з цих станів квазірівноважних процесів дисоціації молекули, про цесів перенесення електрона між високозбудженою молекулою та оточенням (матрицею) тощо. Такі процеси пояснюють вицвітання барвника на тканинах, нестійкість барвників у процесі лазерної генерації тощо. Запропоновано використовувати фотонестабільність барвників для запису інфомації. Дан анализ экспериментальных и теоретических исследований процессов, протекающих при релаксации молекулы из высоковозбужденного состояния, полученного как при одноквантовом (S₀->Sn), так и двухступенчатом (S0 -ʰᵛ> S₁ -> T₁ -ʰᵛ> Tn) возбуждении. В качестве объекта исследования использованы полимерные слои с красителями (резазурин, метиленовый голубой и бриллиантовый зеленый). Отмечено, что в высоковозбужденных электронных состояниях системы могут жить в течение нескольких колебаний, характеризующих данные состояния. Показано, что среди высоковозбужденных состояний молекулы имеются диссоциативные состояния. Это обусловливает протекание из этих состояний квазиравновесных процессов диссоциации молекулы, процессов переноса электрона между высоковозбужденной молекулой и окружением (матрицей) и др. Такие процессы объясняют причину выцветания красителя на тканях, неустойчивость красителей в процессе лазерной генерации и т.д. Предложено использовать фотонестабильность красителей для целей записи информации.